(untitled) (Revista Argentina de Musicología, 2026)
This article explores the multifaceted relationships between the Internationales Musikinstitut Darmstadt (IMD) and various Argentine musical institutions from the 1950s to the 1970s. Through an in-depth analysis of epistolary exchanges, archival documents, and institutional networks, it reconstructs circuits of cultural mediation involving the dissemination of repertoire, pedagogical materials, and publications, as well as the circulation of performers, composers, and collectors. Case studies such as José Habschied in Mendoza, Mario J. A. Galvani in Buenos Aires, the National University of Córdoba, and the Jornadas Americanas de Música Experimental demonstrate how Darmstadt’s symbolic authority was transformed into cultural, pedagogical, and performative capital in the Southern Cone. The article also examines cultural diplomacy, editorial transfer, and audience-building dynamics that positioned Argentina as an active node within the transnational networks of new music. Editorial History: Received: October 24, 2025 Accepted: May 27, 2026